Frequent Mental Distress, Chronic Conditions, and Adverse Health Behaviors in the Behavioral Risk Factor Surveillance Survey, Jordan, 2007 - Mohannad Al-Nsour, MD, MSc; Meyasser Zindah, MD; Adel Belbeisi, MD; Italia V. Rolle, PhD, RD; Henry Walke, MD, MPH; Tara Strine, PhD, MPH; Geraldine S. Perry, DrPH, RD; Bassam Jarrar, MPH; Ali Mokdad, PhD (Preventing Chronic Disease, 2013)
Introduction Recent evidence indicates that chronic diseases and mental illness are associated. In the Middle Eastern country of Jordan, chronic diseases and frequent mental distress (FMD) are increasing; however, the capacity for mental health care is limited. The objective of this study was to determine the association between FMD, chronic conditions, and adverse health behaviors in Jordan. Methods The third cycle of the Jordan Behavioral Risk Factor Surveillance Survey (2007) served as the data source for this study. The sample consisted of 3,612 noninstitutionalized Jordanian adults aged 18 years or older. Logistic regression was used to obtain odds ratios for the association between chronic conditions, health behaviors, and FMD adjusted for age, sex, marital status, education, income, and employment. Results In the adjusted models, people with hypertension (adjusted odds ratio [AOR], 2.0; 95% confidence interval [CI], 1.6–2.7), high cholesterol (AOR, 2.3; 95% CI, 1.6–3.2), diabetes (AOR, 1.6; 95% CI, 1.1–2.4), and asthma (AOR, 2.2; 95% CI, 1.5–3.1) and smokers (AOR, 1.5; 95% CI, 1.1–2.0) were more likely to have FMD than people without each of these conditions. Adults who reported vigorous physical activity were less likely to have FMD (AOR, 0.6; 95% CI, 0.4–0.9) than their less active counterparts. Conclusions In Jordan, FMD was associated with several chronic conditions. As a result, we suggest additional research to examine the complex relationship between FMD and chronic conditions. More doctors in the primary health care system should be trained in mental health.